Stress and burnout in family medicine trainees in the North of Portugal: a cross-sectional study - Mendes, Paula (2017)
Objectives: To determine the prevalence of burnout among family medicine trainees in the north region of Portugal and to test possible associations of burnout with sociodemographic and occupational factors and stress. Type of study: Cross-sectional. Location: Northern Portugal. Population: Family medicine trainees. Methods: We used a convenience sample of the trainees attending meetings of the residency program from 3 November to 11 December 2009. We used the Maslach Burnout Inventory and the Stress in Health Professionals questionnaire and collected sociodemographic and professional data. The prevalence of stress and burnout were calculated and associations between job stress and burnout were tested. Results: We studied a sample of 210 trainees (68% of the population) of whom 72% were female. The response rate was 92.5%. Most trainees reported moderate stress (n=127, 60.5%), especially in training activities and in dealing with patients. The prevalence of burnout in trainees ranged between 8.6% (95%CI 4.8-12.4) and 34.3% (95%CI 27.9-40.7), depending on the definition used. We found that 29.8% (95%CI 23.6-36.0) of trainees had high emotional exhaustion, 17.7% (95%CI 12.5-22.9) had high depersonalization and 43.4% (95%CI 36.7-50.1) had low personal accomplishment. Depersonalization was significantly higher in men (p